Exploring the World of Plane Shapes: A Study on Fourth-Grade Students' Comprehension of Mathematical Concepts - Asmara, Andes Safarandes; Azizah, Nur Lailatul; Fitri, Ayu (Indonesian Journal of Science and Mathematics Education, 2023)
This research investigates the mathematical understanding of fourth-grade students on plane materials using interactive multimedia. Qualitative methods and a descriptive approach are applied to students at MI Ar Rahmah, Bengle Village, Majalaya, during the academic year 2020/2021. Sampling and mathematical comprehension tests are conducted on rectangular and triangular plane materials. The results reveal three levels of understanding: high (47%), medium (21%), and low (32%). The analysis shows that high and medium-level students fulfill indicators with errors, while low-level students only meet the concept application indicator. Student interviews uncover difficulties in grasping concepts, including recognizing objects and modeling mathematical statements. Hence, improved teaching methods are needed to enhance students' mathematical understanding, particularly in plane materials. Further research is recommended to explore effective strategies for reducing mathematical anxiety and enhancing students' conceptual understanding.